The effectiveness of a guidance program to correct bullying behavior in Wasit intermediate schools - Assist. Lectr. Wisam Salih Mahdi (Journal of College of Education, 2025)
The researcher aims to demonstrate the effectiveness and value of a guidance program implemented by educational counselors in middle schools in Wasit Governorate in Iraq to reduce the severity of bullying in students’ behavior among themselves, and to address abnormal cases. The importance of the research is evident in examining the conditions of students between the ages of 13 and 15 years and their need for attention and guidance care. The descriptive analytical approach and the applied, fragmented approach were used to present the program in 8 guidance sessions for a random sample of 182 middle school students distributed across 3 schools in Wasit Governorate. They were divided into experimental classes with 93 students and control classes with 89 students. The results showed that there were statistically significant differences between the students in the experimental classes who followed the guidance program in terms of a decrease in bullying rates and the students in the control classes who did not follow the program. It also showed the need for educational guides and advisors to have training and rehabilitation sessions to develop their guidance performance in dealing with behavioral cases such as bullying, discrimination, and excessive aggression. It also revealed the presence of extreme bullying, sometimes widespread among students, reflecting the wealth and status of their parents. This behavior is not related to gender, and there are deficiencies in the performance of supervisors due to administrative pressures, especially in government schools with overcrowded classrooms, which hinders the supervisor’s work. The researcher recommended the importance and necessity of holding training sessions for educational supervisors by the Education Directorate, addressing how to address student behavior and shift it from a negative to a positive framework, and developing guidance programs for students in the intermediate and preparatory stages